2010
DOI: 10.17761/ijyt.20.1.w33375003846vt18
|View full text |Cite
|
Sign up to set email alerts
|

The Art of Yoga Project: A Gender-Responsive Yoga and Creative Arts Curriculum for Girls in the California Juvenile Justice System

Abstract: As girls enter the juvenile justice system, they stand on the precipice of a lifelong cycle of crime and incarceration, yet still have the opportunity to turn toward healing and rehabilitation. With this in mind, The Art of Yoga Project (AYP) has designed a gender-specific intervention that combines Yoga, visual arts, and creative writing to help girls learn how to create a positive future for themselves. This article introduces AYP and shares the goals, objectives, and experiences of the program. A thorough d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Some studies have found that surveys collected soon after detention are contaminated by bravado and a defensive attitude and might, therefore, reveal little about the individual’s actual state of mind (Harris & Fitton, 2010). Sometimes, in subsequent surveys, respondents tend to be more genuine in their responses, and this can make the individual appear to have deteriorated with treatment rather than having made any therapeutic gains (Harris & Fitton, 2010). A third round of questioning may produce more honest answers in response to program participation and increased self-awareness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have found that surveys collected soon after detention are contaminated by bravado and a defensive attitude and might, therefore, reveal little about the individual’s actual state of mind (Harris & Fitton, 2010). Sometimes, in subsequent surveys, respondents tend to be more genuine in their responses, and this can make the individual appear to have deteriorated with treatment rather than having made any therapeutic gains (Harris & Fitton, 2010). A third round of questioning may produce more honest answers in response to program participation and increased self-awareness.…”
Section: Discussionmentioning
confidence: 99%
“…The AYP’s (Harris & Fitton, 2010; Harris, Kaplan, & Epstein, 2016; Murtagh, 2016) YCAC combines gender-responsive best practices with trauma-sensitive yoga, creative expression through art, and journaling. The AYP’s mission is to address emotional dysregulation while improving self-control, self-awareness, and self-respect.…”
Section: Art and Expressionmentioning
confidence: 99%
See 1 more Smart Citation